Tree growth as an effect indicator of silvopastoral systems in the low hilly area of western Henan province, China - Liu, Peisong; Cheng, Fan; Wang, Xinlong; Liu, Zhipeng; Cheng, Liping; Tong, Weishuang; Qi, Guang; Kou, Lixuan (Frontiers in Forests and Global Change, 2023)
The low hilly area is a major landform in the western of Henan province, China, and it is suffering soil and water loss because of human activities. The silvopastoral system that combines trees and grasses has been widely used to restore these fragile areas. We conducted a field in situ experiment involving pure forest of Populus simonii (PS; Salicaceae), Platycladus orientalis (PO; Cupressaceae), Quercus variabilis (QV; Fagaceae) and Robinia pseudoacacia (RP; Fabaceae), and each forest tree species combining Medicago sativa (MS; Fabaceae) as silvopastoral system, i.e., PS-MS, PO-MS, QV-MS and RP-MS in 2011 in the low hilly area of Henan province. We recorded tree diameter at breast height (DBH), tree height (TH) in the year 2014 ~ 2016, 2018, 2020 and 2022 for all the different vegetation types. Tree biomass load (TBL, i.e., tree biomass per unit area) was estimated based on DBH and TH using allometric equation for each tree species. Generally, the results showed that the DBH, TH and TBL were promoted in the silvopastoral system (PS-MS, PO-MS and QV-MS). Specially, the DBH and TBL of PS-MS and PO-MS tend to be higher and were significantly higher than the pure forest of PS and MS respectively in 2014-2016; the silvopastoral system was not significantly different with pure forest for DBH in 2018 and 2022, and for TBL in 2018 and 2020. TH was lower in the PS-MS and PO-MS than PS and PO in 2014-2016, while in 2018, 2020 and 2022 there were no difference or higher in the silvopastoral system than the pure forest. The DBH, TH and TBL were all higher in QV-MS than QV. The TBL in the RP-MS was non-significant or lower compared to RP. Moreover, the TBL tends to be lower in upslope than downslope positions in pure forest, while there is no difference in most silvopastoral system. In summary, PS and PO may be suggested to as the tree species selection in vegetation restoration process for about five years, and the QV may be a better alternative for a long term, while RP may not be selected.